Epidemiological Investigation on Rabies Deaths in Berasia Block, Bhopal - Brajendra Mishra (Medsci Publications, 2012)
Background: In rural area of a community block, four rabies deaths within 19 days following exposure, in spite of receiving Post exposure Prophylactic vaccination warranted epidemiological investigation and situational analysis to take up remedial measures if any. Methodology: A detailed epidemiological study was planed. The component of the study included eco-geographical evaluation of the study area by visit, post exposure clinic-epidemiological evaluation of survivors by clinical examination and interview, verbal autopsy from the kith and kin of the four dead cases, enquiries on practice of standard protocol by health providers an health seeking behaviour of the cases/families involved through interview and immunological analysis for measuring the titers of antirabies antibodies in sera of some patients following exposure/vaccination. All the 36 cases bitten by rabid Jackal were contacted and interviewed. Family contacts of all four who died were also interviewed. Block Medical Officer of the area was also interviewed. Result: It was found that man made alterations in eco- geographical features were leading to increase in exposure risks to sylvatic rabies. It was found that standard protocol for Post Exposure Prophylaxis was not in practice and health providers and other related agencies needed reorientation on conduct of post exposure prophylaxis. It was found that population living in high risk zone needs to be educated on immediate care to be taken after exposure and modify their own health seeking behaviour by not visiting the quacks.